A Review of Milled Rice Demand and Supply of Some ASEAN Countries and Lesson Learnt for Cambodia - Sros, Em; Mardy, Serey; Chanthuch, Try (Cattleya Darmaya Fortuna, 2024)
Rice is a vital crop for ASEAN countries, serving as a primary source of food security and playing a significant role in the regional economy. To draw lessons for rice supply and demand in Cambodia, this article will examine and briefly describe the rice markets in different ASEAN nations, including import and export, rice milling technology, government policy, obstacles, and opportunists. In Cambodia, a program utilizing the sustainable rice cluster (SRC) approach has been developed and put into action by the government in order to maintain the rise of rice production. Compared to traditional approaches, SRC has enhanced rice cultivation by about 40%. The key lessons Cambodia can learn are boosting domestic production, diversifying rice varieties, improving storage and distribution, practicing climate-smart practices, strengthening regional cooperation, improving market access, and farmer empowerment. By analyzing rice demand and supply dynamics in ASEAN and applying the lessons learned, Cambodia can strive to achieve self-sufficiency in rice production and reduce reliance on imports, increase the profitability and competitiveness of the rice sector, enhance food security for its population, and contribute to regional food security within ASEAN.